Viscoelastic characteristics of whey protein systems at neutral pH - Fernandes, Paulo B. (2011)
The gelation properties of whey proteins alone and in presence of NaCl, KCl, CaCl2 and L-lysine upon heating to 80°C were characterised at pH 7 by oscillatory shear measurements. At the sol—gel transition, the whey protein system gave G′(ω) and G″(ω) curves with a slope of 0.5–0.6. For higher concentrations the gel behaviour was typical for an homogeneous network and whey protein gels present a gel structure with a fractal dimension of 2.7. NaCl, KCl, CaCl2 and L-lysine increased the elasticity of whey protein gels in a similar way. At ionic strength 0.03 the Na-, K- and L-lysine-WP gels obtained were transparent, while the Ca-WP gels presented an opaque particulate structure.